Discovery Learning sebagai Inovasi Model Pembelajaran Pendidikan Agama Islam Pasca Pandemi Covid-19 - Iwantoro Iwantoro; Suriadi Rahmat; Abdul Haris (Yayasan Letiges Konsultan Sosial, 2022)
This study aims to describe the discovery learning model as a form of innovation in learning that can be implemented after the Covid-19 pandemic along with its advantages and disadvantages. This research uses a qualitative approach with the type of library research. The results of the research can be conveyed as follows: (1) the discovery learning model is a model for developing active student learning by discovering themselves, investigating themselves, then the results obtained will be loyal and long-lasting in memory, will not be easily forgotten by students; (2) this learning syntax is stimulation, problem statement, data collection, data processing, verification, and generalization; and (3) this discovery learning model has many advantages, besides that it also has disadvantages but it has more advantages so that this learning model is very good to be applied in PAI learning.